2021
DOI: 10.3390/cells10030549
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Catecholamine Pathway in Glioblastoma Development

Abstract: Glioblastoma (GBM) is the most aggressive tumor of the central nervous system (CNS). The standard of care improves the overall survival of patients only by a few months. Explorations of new therapeutic targets related to molecular properties of the tumor are under way. Even though neurotransmitters and their receptors normally function as mediators of interneuronal communication, growing data suggest that these molecules are also involved in modulating the development and growth of GBM by acting on neuronal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 77 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…None of the patients were alive at the time of the initiation of the original epigenomic analyses in 2018–2019 [ 5 ]; the histological diagnoses of the obtained tumor specimens were based on the 2016 WHO guideline [ 12 ]. As additional immunohistochemical studies were subsequently also performed and reported on the same tissue specimens [ 5 , 6 , 7 ], no sufficient tissue remained for complementary testing of those molecular alterations (i.e., H3F3A, HIST1H3B, HIST1H3C, TERT, EGFR-amplification) recommended in the 2021 WHO revision [ 13 ]. As Table S1 shows, however, all tumors were late-onset GBMs, and thus mutations in histone proteins would be very unlikely.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…None of the patients were alive at the time of the initiation of the original epigenomic analyses in 2018–2019 [ 5 ]; the histological diagnoses of the obtained tumor specimens were based on the 2016 WHO guideline [ 12 ]. As additional immunohistochemical studies were subsequently also performed and reported on the same tissue specimens [ 5 , 6 , 7 ], no sufficient tissue remained for complementary testing of those molecular alterations (i.e., H3F3A, HIST1H3B, HIST1H3C, TERT, EGFR-amplification) recommended in the 2021 WHO revision [ 13 ]. As Table S1 shows, however, all tumors were late-onset GBMs, and thus mutations in histone proteins would be very unlikely.…”
Section: Methodsmentioning
confidence: 99%
“…Methylomes of five epilepsy surgery specimens (CG) obtained from the European Nucleotide Archive [ 14 ] ( , Primary Accession: PRJNA391429; EGAS00001002538 accessed on 17 June 2022) were used as controls in the DNA CpG methylation analyses in comparisons with GBM prim and GBM rec [ 5 , 6 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kraboth and colleagues [ 8 ] explore the role of DNA CpG methylation in modulating the expression of neurotransmitters in GBM. These molecules have a well-known role in CNS development and physiology but have been found to be equally important in GBM, due to their interplay with neurons and glioma cells [ 9 , 10 ].…”
mentioning
confidence: 99%